Analisis Pola Tubuh Pekerja di Toko Sembako Jawi Menggunakan Metode Rapid Upper Limb Assessment - Mark Landon, Viko S; Erik Nugraha, Asep (Fakultas Teknik Universitas Tulang Bawang, 2024)
This study aims to analyze the risk of body position patterns in Toko Sembako Jawi workers using the Rapid Upper Limb Assessment (RULA) method. Through the distribution of Nordic Body Map (NBM) questionnaires and interviews, factors causing pain at work were identified, particularly due to repetitive lifting activities with a load of 7-10 kg. The RULA method was applied to evaluate the work posture of the worker's upper body. The results of the analysis showed that the job was high risk with a grand score of 7, indicating the need for immediate investigation and remedial changes. Recommendations included improvements to the upper body positioning pattern by providing better direction to workers as well as suggestions for changes to the work environment, including the use of assistive devices in the work such as folding trolleys and back support belts. By identifying risks and providing recommendations for improvement, this study is expected to improve ergonomic conditions and prevent injuries to the musculoskeletal system of Toko Sembako Jawi workers. Keywords : Body Position Patterns, Musculoskeletal, RULA Method.